(untitled) (Research, Society and Development, 2021)
Objective: To analyze in the national and international literature the quality of life of elderly people with Chronic Renal Failure in the period from 2015 to 2020. Method: This study is a descriptive, qualitative, type of Integrative Literature Review (RIL). To explore the material and categorize the studies, the IRaMuTeQ software was used. Results: 4 classes were formed, namely: The size and factors that affect the quality of life of elderly with chronic kidney disease; The limitations and restrictions caused by the hemodialysis process; Quality of life of elderly patients with CRF associated with dialysis and Communication between family members and professionals to provide care. The content was incorporated through the Descending Hierarchical Classification, by means of a dendrogram, prepared by the authors, in which it represents the frequency of the words (f) and the chi-square value (x2). Conclusion: The quality of life of elderly people with CRF is an important aspect, as these patients have limitations related to the disease and also to treatment by hemodialysis. For this reason, this study addresses subsidies so that health professionals can identify the factors that interfere in the quality of life of elderly people with CRF in order to have a positive evolution and an appropriate treatment.